2023
DOI: 10.14267/turbull.2023v23n2.5
|View full text |Cite
|
Sign up to set email alerts
|

A lassú turizmus szakirodalmi áttekintése

Eylül Balaban,
Krisztina Keller

Abstract: A tanulmány célja a lassú turizmus szakirodalmi áttekintése, amely során a Scimago és a ScienceDirect adatbázisokban megtalálható Q1 és Q2 szintű folyóiratokban 2010-2021 között angol nyelven megjelent tanulmányok kerültek vizsgálatra. A kutatás során 63 tanulmány vonatkozásában kerültek elemzésre a témakörben született publikációkat tartalmazó folyóiratok, a szerzők száma, a kulcsszavak, a kutatási módszerek, a vizsgált földrajzi kontextus és a témakörök. Elmondható, hogy a lassú turizmus, mint kutatási téma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The study demonstrates that slow thinking -valuing quality over quantity -is the basis of slow tourism (Serdana, Maccarone-Eaglen, & Sharifi, 2020). In their literature review on slow tourism, Balaban and Keller (2023) examined 63 studies in international journals over the past decade and found no uniformly accepted definition of slow tourism. Instead, the authors identify several directions:…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study demonstrates that slow thinking -valuing quality over quantity -is the basis of slow tourism (Serdana, Maccarone-Eaglen, & Sharifi, 2020). In their literature review on slow tourism, Balaban and Keller (2023) examined 63 studies in international journals over the past decade and found no uniformly accepted definition of slow tourism. Instead, the authors identify several directions:…”
Section: Literature Reviewmentioning
confidence: 99%